Indo-Bhutan relations and China interventions - Yadav, Lal Babu. (New Delhi, India : Anmol Publications, 1996)
During Colonial Regime India Was Immensely Influenced With Western Concepts Of Relations. In Border Environment These Concept Of Relations Virtually Embraced Every Branch Of Human Activity- Whether It Is Just Promotion Of Products Or Image Building For Individuals, Corporate Bodies Government And Even Political Parties.The Book Faithfully Illustrates In A Succinct And Reliable Manner The Historical Background Chinese And Indian Policies Towards Bhutan. It Also Details The India- Bhutan Relations. It Seriously Examines The Chinese Claims On Bhutanese Territories And The Correct Position Of Bhutan In Present Perspectives.Due To Beautiful Treatment Of Historical Facts Keeping The Social, Political Aspects Of The Problem In View, It Will Be Highly Useful To The Academics In The Field Of International Relations, Trade And Economics As Well As Student And Research Scholars Of History.
Includes bibliographical references
Keywords: India -- Foreign relations -- Bhutan; Bhutan -- Foreign relations -- India; China -- Foreign relations